Bank Efficiency and Market Structure : What Determines Banking Spreads in Armenia? - Floerkemeier, Holger (IMF Working Papers; Working Paper ;, 2007)
Despite far-reaching banking sector reforms and a prolonged period of macroeconomic stability and strong economic growth, financial intermediation in Armenia has lagged behind other transition countries, and interest rate spreads have remained higher than in most Central and Eastern European transition countries. This paper examines the determinants of interest rate spreads and margins in Armenia using a bank-level panel dataset for the period 2002 to 2006. We find that bank-specific factors, such as bank size, liquidity, and market power, as well as the market structure within which banks operate, explain a large proportion of crossbank, cross-time variation in spreads and margins. The results suggest that there is a large potential to increase cost efficiency and competition in the banking system.